Managing COVID-19 with Traffic transport Measures - Azam Mohamadloo; Zahra Batooli; Gholamreza Mostafaii (Unnes Journal of Public Health, 2023)
Background: Since transmission of the virus occurs by interaction among individuals, the transportation system is the main factor in the spread of the COVID-19. The purpose of the study was to explain traffic transport measures to managing COVID-19 in Iran. Method: We first received the approvals of the Iran Committee against COVID-19. Then, measures of travel restrictions in 120 approvals were selected and categorized by the research team. Results All the measures associated with travel restrictions were elicited from the data analysis and were classified into four categories, including private transportation within the city, travel by private transportation means, travel between countries, and public transportation. Conclusion Travel restrictions have a severe impact on the sector, causing major dysfunction in activities at airlines and airports and significantly increase the risk of failure for air transport-related businesses. Therefore, developing the strategies to correct and re-orientate their businesses is urgently necessitating. To decrease the impacts of the COVID-19 pandemic, it is necessary the engagement of citizens, the private sector, governments at all levels, as well as international agencies, and all other related organizations.